Cognitive reserve-mediated neural modulation of emotional control and regulation in people with late-life depression. Issue 8 (11th October 2019) - Huang, Chih-Mao; Fan, Yang-Teng; Lee, Shwu-Hua; Liu, Ho-Ling; Chen, Yao-Liang; Lin, Chemin; Lee, Tatia M C
Abstract: Late-life depression (LLD) is an affective disorder that is highly prevalent among older people. Cognitive reserve (CR) refers to an active process that facilitates the flexibility and efficiency of the neural networks to compensate for impairments that emerge in consequence of brain pathology. The current functional magnetic resonance imaging study investigated whether and how CR affects emotional regulation, level of depression severity and neural activity associated with affective control during emotional Stroop (eStroop) task. Altogether, 90 older people participated in this study, 50 of whom suffered from LLD. We used years of education and verbal fluency capacity as proxies for CR. Clinical participants with relatively higher CR presented with milder degrees of depression, better eStroop performance and stronger neural activity in the middle frontal gyrus (MFG) involved with exercising affective control. Results of the mediation analysis indicated that both education and verbal fluency significantly mediated the association between the depression severity and MEG activity. These results suggest a negative association between CR and age-related clinical symptoms of emotional dysregulation. Our neurobehavioral findings provide supportive evidence that CR implies efficiency of top-down emotional regulation and operates as a protective factor against emotional and cognitive vulnerability in the aging brain.